Not as Bad as It Seems? A Literature Review on the Case of Microplastic Uptake in Fish - Müller, Carolin (Frontiers in Marine Science, 2021)
Within the past decade, microplastic (MP) particles (<5 mm in size) became the focus of both scientific and public attention, on one hand due to their cumulative industrial application and global presence, on the other hand due to their size range allowing the interaction with organisms at the base of the marine food web. Along with the growing evidence of their ubiquitous distribution, the ingestion of MP fibers and fragments has been verified for a variety of marine biota, with fish species being among the group of organisms most intensively studied both in the laboratory and in the field. While the gross of scientific literature focuses on the quantification and chemical characterization of MP in the gastrointestinal tract of fish, in-depth investigations on the impacts or a contextualization of ingestion are rarely accomplished. Yet, the constant media-coverage and omnipresence of the topic present a (threat) scenario among civil society which might lack a solid scientific foundation. This review, therefore, analyses the scientific output of 90 field studies covering 487 different fish taxa with due regard to explanatory variables for MP ingestion. Additionally, it highlights persistent knowledge gaps in relation to the examination of in-situ ingestion effects and proposes measures how to approach them in future research initiatives. Moreover, the potential existence of a publication bias and a consequent distortion of the perception of the topic is evaluated.